Influences of 3D Sub‐Grid Terrain Radiative Effect on the Performance of CoLM Over Heihe River Basin, Tibetan Plateau. (17th January 2022) - Zhang, Xindan; Huang, Anning; Dai, Yongjiu; Li, Weiping; Gu, Chunlei; Yuan, Hua; Wei, Nan; Zhang, Yanlin; Qiu, Bo; Cai, Shuxin
Abstract: Surface solar radiation (SSR), as a primary component of heat budget between land and atmosphere, controls both water and energy exchanges. However, the sub‐grid terrain radiative effect (STRE) which exerts critical influences on SSR simulation is usually extremely simplified or even ignored in most current land surface models (LSMs) due to the heavy computational burden. In this study, we developed a physically realistic and computationally efficient three dimensional (3D) STRE scheme and implemented it into the Common Land Model (CoLM) to indicate its quantitative influences on surface energy budget, land surface temperature (LST), soil temperature, and moisture simulations over the Heihe River Basin, Tibetan Plateau. Results show that the CoLM coupled with 3D‐STRE scheme shows more realistic description of SSR and improves the simulation of soil thermal and moist features at both single‐point and regional scales. Compared to the results without 3D‐STRE, the inclusion of 3D‐STRE scheme efficiently diminishes the overestimation of SSR, which leads to the root mean square error (RMSE) of LST simulation reduced by 17.1% due to significant improvements in valley areas. Adopting 3D‐STRE scheme also improves the pattern and amplitude of temporal variability of simulated soil temperature (moisture) at 37 sites with the mean Taylor score increased by 3.6–3.7% (14.0–14.3%). These results emphasize the importance of considering the 3D‐STRE scheme in LSMs and are significantly helpful to deepen our understanding of surface heat exchanges and improve the representations of land surface processes over complex terrain. Plain Language Summary: Topography exerts remarkable influences on the land surface solar radiation (SSR) over complex terrain, which controls both water and energy exchanges between land and atmosphere. However, the parameterization of sub‐grid topographical effects on SSR are usually extremely simplified or even ignored in most current numerical models due to the heavy computational burden. In this study, we developed a parameterization with much more real physical processes, simple parameters and high computational efficiency to consider the impact of sub‐grid topography on SSR, it tends to show widely potential application in land process and climate modeling. Taking the Heihe River Basin in China as an example, we found that the land surface model coupled with this scheme shows more realistic description of SSR and significantly improves the simulations of soil thermal and moist features. These results highlight the necessity of considering the sub‐grid topographical effects on SSR simulation in land surface modeling and are obviously helpful to advance our understanding of the surface heat exchanges and improve the representations of land surface processes over complex terrain areas. Key Points: A 3D sub‐grid terrain radiative effect (STRE) scheme is developed The 3D STRE scheme can show more realistic description of the land surface solar radiation The CoLM coupled with the 3D STRE scheme significantly improved the simulation of soil thermal and moist features over complex terrain areas